PROVIDING HEALTH EDUCATION TO PARENTS AND TEACHERS ON HANDLING TANTRUMS IN TODDLERS - Sholikhah, Siti; Putri, Meri Selviani; Putri, Hany Syafira Daniara; Astary, Karin Mitha; Firmansyah, Rahmat Agung; Suhartini, Suhartini; Irfan, Nur Muhammad (Journal of Community Research and Engagement, 2024)
A tantrum in children is a way for them to express their feelings, as they are not yet able to communicate effectively. Tantrums often occur in toddlers and preschool-aged children, typically between 3-4 years old. Community service was provided to parents and teachers through health education on how to handle tantrums in children. This activity was conducted with the hope that parents and teachers would be better able to understand the children. The community service was carried out through lectures and question-and-answer discussions. The results of this community service showed a 43% increase in knowledge after the health education was provided. There was an increase in the knowledge of parents and teachers regarding how to handle children experiencing tantrums. Health education has a significant impact on the knowledge of parents and teachers, helping them develop positive coping mechanisms when dealing with children having tantrums.